Caudal epidural catheterization for pain management in 48 hospitalized horses: A descriptive study of demographics, complications, and outcomes - Douglas, Hope; Midon, Monica; Shroff, Kavita; Floriano, Dario; Driessen, Bernd; Hopster, Klaus (Frontiers in Veterinary Science, 2022)
The placement of caudal epidural catheters in horses has become more frequent as a multi-modal analgesic strategy. Despite its integration into clinical practice, there are limited reports describing the use of caudal epidural catheterization for prolonged use in horses. The purpose of this study was to characterize the hospitalized caseload undergoing epidural catheterization for long-term epidural analgesic administration, to report the response to epidural therapy and observed complications, and to describe patient outcomes. Medical records of hospitalized equine patients that underwent placement of a caudal epidural catheter for analgesic management between 2017 and 2021 were analyzed retrospectively. For the 62 catheters placed in the 48 cases, the most frequent diagnosis category prompting epidural analgesia was orthopedic (43/48, 89.6%). Synovial sepsis was the most frequent specific diagnosis prompting epidural catheter placement (11/48, 22.9%). The initial response to epidural therapy was characterized as positive for 37/62 (59.7%) catheters. Complications were documented for 46/62 (74.2%) catheters. However, most of these complications were classified as mild (51.6%) or moderate (14.5%), and exaggerated physiologic responses were observed most frequently. Of the horses studied, 52.1% survived to be discharged from the hospital. With awareness of potential complications and vigilant monitoring, caudal epidural catheters should be considered for equine patients as an analgesic strategy.